Hypothermia in Uremic Dogs and Cats. (2nd August 2016) - Kabatchnick, E.; Langston, C.; Olson, B.; Lamb, K.E.
Abstract : Background: The prevalence of uremic hypothermia (UH) and the effects of improving uremia on body temperature have not been determined in veterinary patients. Objectives: To determine the prevalence of UH and correlations between uremia and body temperature in patients undergoing intermittent hemodialysis (IHD). Animals: Uremic dogs (n = 122) and cats (n = 79) treated by IHD at the Bobst Hospital of the Animal Medical Center from 1997 to 2013. Methods: Retrospective review of medical records. Results: The prevalence of hypothermia was 38% in azotemic cats and 20.5% in azotemic dogs. Statistically significant temperature differences were observed between uremic and nonuremic dogs (nonuremic: mean, 100.8°F; range, 91.2–109.5°F; uremic: mean, 99.9°F; range, 95.6–103.8°F; P < .0001) and cats (nonuremic: mean, 100.6°F; range, 94.0–103.8°F; uremic: mean, 99.3°F; range, 92.3–103.4°F; P < .0001). In dog dialysis patients, significant models included (1) timing (pre‐dialysis versus post‐dialysis) with weight class (small [ P < .0001], medium [ P = .016], and large breed [ P = .033] dogs), (2) timing with serum creatinine concentration ( P = .021), and (3) timing with BUN concentration ( P < .0001). In cat dialysis patients, there was a significant interaction between timing and weight as a categorical variable (<5 kg and ≥5 kg). Conclusions and Clinical Importance: Uremic hypothermia appears to be a clinical phenomenon that occurs in cats and dogs. Uremic patients are hypothermic compared to ill nonuremic patients and body temperatures increase when uremia is corrected with IHD in dogs and in cats >5 kg. In cats, UH seems to be a more prevalent phenomenon driven by uremia. Uremic hypothermia does occur in dogs, but body weight is a more important predictor of body temperature.